(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
In this article are analyzed the factors of further development and economic efficiency of the system of providing the population of our country with food, including fruits and vegetables, based on improving the organizational and economic mechanism of the fruit and vegetable system.